2021
DOI: 10.3389/fonc.2021.694718
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological Characteristics and Prognosis in Endometrial Cancer With Bone Metastasis: A SEER-Based Study of 584 Women

Abstract: PurposeBone metastasis from endometrial cancer (EC) is rare and poorly described. The purpose of the present study was to investigate the correlation between the clinically accessible factors and survival time among EC patients with bone metastasis.Patients and MethodsWe retrospectively identified and reviewed EC patients with bone metastasis from 2010 to 2016, based on the Surveillance, Epidemiology and End Results (SEER) database. Univariable and multivariable Cox regressions were applied to evaluate the eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 27 publications
1
4
1
Order By: Relevance
“…The multivariate analyses in our study revealed that the non-endometrioid histological subtype emerged as an independent risk factor for lower OS within our study cohort. This finding aligns with the conclusions drawn by Liu et al and Hu et al [6,7], supporting the notion that the non-endometrioid subtype is characterized by more aggressive biological behavior and limited responsiveness to targeted medicines and hormonal therapy when compared to endometrioid EC. Furthermore, the increased susceptibility of nonendometrioid tumors to harbor mutations in the TP53 gene is noted, which, in turn, can contribute to a poorer prognosis [21,22].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The multivariate analyses in our study revealed that the non-endometrioid histological subtype emerged as an independent risk factor for lower OS within our study cohort. This finding aligns with the conclusions drawn by Liu et al and Hu et al [6,7], supporting the notion that the non-endometrioid subtype is characterized by more aggressive biological behavior and limited responsiveness to targeted medicines and hormonal therapy when compared to endometrioid EC. Furthermore, the increased susceptibility of nonendometrioid tumors to harbor mutations in the TP53 gene is noted, which, in turn, can contribute to a poorer prognosis [21,22].…”
Section: Discussionsupporting
confidence: 91%
“…Several studies have been conducted to evaluate the different histopathological, clinical status, and treatment outcomes of the EC population. Studies have also been conducted to study the EC population with distant metastasis in the bone and lungs; however, there is still a lack of studies on liver metastasis [7]. This study was performed using the Surveillance, Epidemiology, and End Results (SEER) database to evaluate and assess the clinical features and prognostic factors of EC patients with liver metastasis.…”
Section: Introductionmentioning
confidence: 99%
“…Patients over 60 years old are generally considered the elderly. Based on previous literature (27,28), we divided the patients' age into >60 years old and ≤60 years old for convenient analysis. Although some researchers reported tumor site was an independent survival predictor of PC (29)(30)(31), our multivariate Cox regression analysis showed that tumor site was not correlated with OS or CSS in patients with PCBM.…”
Section: Discussionmentioning
confidence: 99%
“…Although some researchers reported tumor site was an independent survival predictor of PC (29)(30)(31), our multivariate Cox regression analysis showed that tumor site was not correlated with OS or CSS in patients with PCBM. For convenient analysis, patients' tumor size were divided into<5 and ≥5 cm based on previous literature (21,28). However, univariate Cox regression analysis showed tumor size was not correlated with survival.…”
Section: Discussionmentioning
confidence: 99%
“…The SEER database includes population-based data from 18 registration centers, which covers approximately 30% of the US population. 12 The SEER database includes data on demographics, cancer incidence, tumor-related clinicopathological features, and cancer treatment, thereby providing accessible information for clinical studies of malignant tumors, especially for rare tumor entities. 13 Ethical approval was obtained from the Ethics Committee of the Affiliated Hospital of the Medical School of Ningbo University.…”
Section: Methodsmentioning
confidence: 99%